Avaliação do potencial de grãos defeituosos de café como substratos na produção de fibras com potencial antioxidante - Adalberto Moraes Moreira Penna (2015)
Considering all the countries that produce coffee, Brazil holds the first position, being responsible for 33,6% of the global yield. Coffee's processing, like the processing of any other agricultural product, generates byproducts that can be a problem in a economic, social and environmental points of view. Many researches have the objective of finding new uses to coffee's pulp, husks, silverskin and spent coffee grounds. Defective coffee beans are not always considered a coffee byproduct and are incorporated into blends designed for the internal market, making the coffee's quality to decrease. There are few studies designed towards finding alternative uses for them, but since the demand for fiber enriched products is increasing and coffee often exhibits a good amount of antioxidant compounds, a new application arises for this byproduct. The objective of the present study was to evaluate the potential of the defective coffee beans as a source of dietary fibers with antioxidant capacity. The beans were sorted according with the different types of defects and analyzed separately. Healthy beans and a sample of beans rejected during processing were also analyzed for comparison purposes. The samples were blanched, dried and grinded until the obtainment of a powder with proper particle size. Centesimal analysis (moisture, lipids, ash, protein and fibers), technological properties (oil absorption index, water absorption index, swelling capacity and solubility index), colorimetry, total polyphenol content and antioxidant activity (DPPH, ABTS) were determined for all the samples. Total fiber content were between 49,88-62,69%, a relatively high value when compared with other raw material and agricultural wastes. The samples also had good hydratation properties, encouraging its implementation on foods where gel formation is desirable. Results from spectrophotometric analysis indicate that the antioxidant activity is relatively high with no difference between the sample of rejected coffee beans and healthy beans. Black beans exhibited inferior antioxidant capacity when compared with the rest.